City Water Matters Cultures, Practices and Entanglements of Urban Water - Watson, Sophie (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Water is one of the most pressing concerns of our time. This book argues for the importance of water as a cultural object, and as a source of complex meanings and practices in everyday life, embedded in the socio-economics of local water provision. Each chapter aims to capture one element of water's fluid existence in the world, as material object, cultural representation, as movement, as actor, as practice and as ritual. The book explores the interconnectedness of humans and non-humans, of nature and culture, and the complex entanglements of water in all its many forms; how water constitutes multiple differences and is implicated in relations of power, often invisible, but present nevertheless in the workings of daily life in all its rhythms and forms; and water's capacity to assemble a multiplicity of publics and constitute new socialities and connections. Cities, and their inhabitants, without water will die, and so will their cultures.